Clinical Study on Risk Factors and Fetomaternal Outcome of Severe Preeclampsia in Bangabandhu Sheikh Mujib Medical University - Sultana, Aklima; Koli, Lutfun Nahar Begam; Sayeeda, Syeda (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Background: Preeclampsia (PE) especially severe or early PE, is a leading cause of morbidity and mortality among the mothers and infants.To determine the maternal risk factors and fetomaternal outcome of severe preeclampsia. Methods: It was a case control study, done in a tertiary care hospital among 100 patients with severe preeclampsia and normal pregnant women admitted. Sampling technique were consecutive sampling methods. Singleton pregnancy between 28 to 40 weeks of gestation with severe preeclampsia were selected as study patients. Written informed consent was obtained. A questionnaire was completed for each patient including patient's age, gestational age, parity, History of hypertension in family, weight and Body Mass Index (BMI). Maternal complications before or after delivery, and perinatal outcome were also be recorded in the data sheet. Data was analyzed by SPSS-20. Results: Among the 50 cases and 50 controls regarding different risk factors age >34 years, BMI, history of precelampsia, were found significant (p<0.05) between two groups. Among the case group, patients developed eclampsia 2(4.0%) abruptio placenta 3(6.0%) HELLP syndrome 2(4.0%) ascites 4(8%) and oliguria1(2.0). But none of the control group had developed these types of complications. In case group 7(14.0%) patients developed PPH and pulmonary oedema 3(6.0%). In control group 5(10.0%) developed PPH and 1(2.0%) developed pulmonary oedema. It was observed that, in case group 5(12.5%) babies had very low birth weight (<1.5 kg) but not in control group. twenty one (52.5%) of the babies had low birth weight (<2.5 kg) in case group and 8.0% of babies had low birth weight in control group. Most 56.0% of the neonates had APGAR score 4-6 at 1 minute in case group and 12(24.0%) in control group. In case group 17(34%) babies developed birth asphyxia and 15(30.0%) of babies developed prematurity, where in control group 7(14.0%) babies developed birth asphyxia and 3(6.0%) of babies developed prematurity. 32(80.0%) newborn needed admission in neonatal care unit in case group and 10(20.0%) in control group (p<0.05). Take baby in home safely in 35(70.0%) in cases group and 50(100.0%) in control group. Early neonatal death was found in 5(10.0%) in case group and not found in control group. Still birth was 10(20.0%) case group and not found control group (p<0.05). Conclusion: Preeclampsia is a leading cause of both fetal and maternal morbidity and mortality in the developing countries. Maternal and fetal outcome are worse in severe preeclampsia. Chatt Maa Shi Hosp Med Coll J; Vol.17 (1); Jan 2018; Page 23-28